Overlapping Mental Magisteria: Implications of Experimental Psychology for a Theory of Religious Belief as Misattribution - Galen, Luke (Method & theory in the study of religion, 2017)
Subjective religious and spiritual experiences (rs) are believed by many to be reliable indicators of external agency. A set of related phenomena are used to support this view that typically involve intuitions or attributions of mental interaction or experiences with rs agents. The present review integrates empirical findings from the fields of the Cognitive Sciences of Religion, experimental social psychology, and neuropsychology to support the position that individuals misattribute rs thoughts and experiences. That is, these experiences are believed to be veridical indicators of external agency when in fact they are subject to materialistic causal influences. This tendency varies as a function of individual differences and contextual conditions. rs phenomena can be artificially generated in a way that is phenomenologically indistinguishable from spontaneous experiences. Intuitions of external agency are rationalized and confabulated, leaving the mistaken impression of validation by analytic processes. The theoretical and philosophical implications of findings are discussed.